Application of the transposon-associated TnpB system of CRISPR-Cas in bacteria: Deinococcus - Yang, Zi-Qi; Li, Mei-Ju; Ahmad, Faizan; Jin, Chun-Zhi; Li, Taihua; Jin, Feng-Jie; Shin, Kee-Sun; Jin, Long (Frontiers in Microbiology, 2025)
Deinococcus radiodurans is one of the most radioresistant organisms found on Earth to date, showing extreme resistance to damage factors such as UV, drought, and mutagens, and is of great interest to scientists around the world. It was determined that the TnpB protein from D. radiodurans ISDra2 functions as an RNA-guided endonuclease, serving as a functional ancestor for the widely used CRISPR-Cas endonucleases. The CRISPR-Cas system is an “acquired immune system” found in most Bacteria and Archaea, and used in a wide range of biological and medical research fields. Cas12f is the smallest RNA-directed nuclease that is currently known and possesses unique characteristics. There has been extensive research conducted on the origin, classification, and mechanism of action of CRISPR-Cas12f, as well as its application in the field of gene editing. TnpB, as the protein closest to Cas12f in the evolutionary tree, has the potential to be used as a new micro-editing tool. Systematic studies have been conducted on it to develop smaller volumes of precision gene editing and treatment tools. In this review, the research progress, mechanism, and application of TnpB protein in D. radiodurans were reviewed. In addition, the classification of CRISPR-Cas system and the application and function of CRISPR-Cas12f in gene editing are also introduced and summarized.